Exceptionally high Cd levels and other trace elements in eggshells of American oystercatcher (Haematopus palliatus) from the Bahía Blanca Estuary, Argentina - Simonetti, Pia (2015)
Concentrations of six trace metals were determined in the eggshells of American oystercatchers (Haematopus palliatus) from the Bahía Blanca estuary, Argentina. All metals measured in selected samples presented concentrations above the detection limit. Means found for Cu, Pb, Cr, Zn and Ni were as follow: 2.02 ± 0.52, 7.23 ± 2.33, 0.78 ± 0.03, 2.22 ± 1.13 and 6.05 ± 0.89 mg/kg dw. The mean concentrations of Cd found were surprisingly high: 13.28 ± 3.38 mg/kg dw. Previous studies made on prey items of the American oystercatchers showed low to medium concentrations of the six trace metals. This may indicate a possible transfer of the metals that are available in the environment through food chains. Our study indicates that American oystercatchers sequester heavy metals in their eggshells. Therefore the eggshells may be useful as biomonitors for trace metal contamination in the Bahía Blanca estuary.